Maxwell E. Britton (1912-2004) - Schindler, J.F. (ARCTIC, 2004)
Maxwell E. Britton, a well-known and highly respected Arctic research scientist and administrator, died at his home in Arlington, Virginia on March 16, 2004. He was 92. Recognized for his dedication to Arctic research, he pioneered innovative ways of pursuing research under the extreme conditions of the far North. Further, Britton was one of the first scientists to specialize in Arctic ecology. Max Britton was born on January 26, 1912 in Hymera, Indiana . After attending public schools in Hymera, he went to Indiana State College where he received his AB degree in 1934. . He then attended Ohio State University, where he was awarded an MS degree in 1937. His doctorate . was earned at Northwestern University in 1941. Three years earlier, Max had been given an instructorship, which began an association with the faculty at Northwestern University that lasted until 1955. . His last year as a Northwestern faculty member was spent on research leave at Stanford University. While at Stanford, Max was offered a position with the Office of Naval Research (ONR), a position he at first declined but later accepted, with the idea of remaining only two years. . Once Max became engrossed in the Arctic program at ONR, he decided to continue in that position and remained there until 1971. Britton's duties included monitoring the Navy contract with the Arctic Institute of North America (AINA). . He became affiliated with AINA after he retired from ONR. Then in 1974, Max joined the U.S. Geological Survey (USGS). . He retired from the USGS in 1983 to his home in Arlington, Virginia. . Max Britton had an early start as a research scientist. During his freshman year in botany at Indiana State College, he excelled to the point that Dr. Ben Smith, his instructor, offered him a job as a laboratory assistant. . Dr. Smith recommended that Max, continue his research at Ohio State University with Dr. L.H. Tiffany and Dr. E.N. Transeau, both prominent phycologists during the 1930s. . Dr. Tiffany, who moved to Northwestern University as the ...